Maternal Thyroid Dysfunction and Risk of Seizure in the Child: A Danish Nationwide Cohort Study. (28th July 2013) - Andersen, Stine Linding; Laurberg, Peter; Wu, Chun Sen; Olsen, Jørn
Abstract : Thyroid hormones are essential for brain development, and maternal thyroid disease may affect child neurocognitive development. Some types of seizures may also depend upon early exposure of the developing central nervous system, and we hypothesized that maternal thyroid dysfunction could increase the risk of seizure in the child. In a Danish population-based study we included 1, 699, 693 liveborn singletons, and from the Danish National Hospital Register we obtained information on maternal diagnosis of hyper- or hypothyroidism and neonatal seizure, febrile seizure, and epilepsy in the child. Maternal diagnosis of thyroid dysfunction before or after birth of the child was registered in two percent of the singleton births. In adjusted analyses, maternal hyperthyroidism and hypothyroidism first time diagnosed after birth of the child were associated with a significant increased risk of epilepsy in the child. Moreover, hypothyroidism diagnosed after birth of the child was associated with a significant increased risk of neonatal and febrile seizures. No significant association was seen for maternal diagnosis prior to birth of the child. We speculate if some degree of maternal thyroid dysfunction was already present during the pregnancy in mothers diagnosed after birth of the child and if this untreated condition may present a neurodevelopmental risk.